Demand for Reinsurance in UK property-casualty insurance industry - WU, RENFENG (2011)
Reinsurance demand has been one of the most controversial issues in the ground of finance during the past decades. Many researchers have analyzed the relationships between many reinsurers‘ financial factors and their reinsurance purchases. These existing researches give a briefly structure when dealing with reinsurance problems. With the objective to provide an insight look into factors influencing reinsurance levels in insurance companies; this study analyzed the level of reinsurance among 468 UK property-casualty insurance companies within a 25 year time scale. Regression analysis is employed as the basic model in the research. In addition, this study measured the relationships between reinsurance demands and other financial factors through a financial management way, as well as a risk management process, which give another aspect when using reinsurance.